New polymorphic psyllipsocids from Burmese amber (Psocodea: Psyllipsocidae). (April 2018) - Hakim, Marina; Azar, Sahar; Maksoud, Sibelle; Huang, Diying; Azar, Dany
Abstract: Annulipsyllipsocus andreneli gen. et sp. nov. and A. inexspectatus gen. et sp. nov., the first records of the Psyllipsocidae from the Cretaceous amber of Myanmar are described, illustrated and their taxonomic position discussed. The new genus is characterized by antennae with 16 segments; flagellomeres with secondary annulations; radial cell closed, five-angled, bulged on its R1 border; triangular pterostigma. Species belonging to Annulipsyllipsocus gen. nov. are polymorphic. The described taxa represent the earliest evidence for polymorphism in Psocodea. A checklist of all known species of Psyllipsocidae is given.